Seasonal Variations in the Physico-Chemical Parameters of Malgujari Pond of Ghugus, District Chandrapur (Maharashtra) - Durge, L. S.; Chilke, A.M.; Chavhan, R. N. (International Journal of Scientific Research in Biological Sciences, 2018)
A Malgujari pond,situated at the heart of Ghugus,an industrial town from district Chandrapur of Maharashtra has been selected for the study of seasonal variations in physic-chemical parameters of water. The period of the study is from December 2015 to November 2017. The following parameters viz-temperature, pH, transparency, conductivity, DO, free CO2, BOD,COD, total hardness, chlorides, phosphate, sulphate and nitrates has been taken for the analysis. The present study showed that the atmospheric temperature is higher than that of water. It is maximum during summer while the minimum in the winter season. Conductivity, pH and BOD are also observed maximum in summer while minimum in winter. DO as well as transparency is found maximum in the winter and minimum in monsoon. Free CO2, BOD, COD, hardness, chlorides, phosphates, sulphates and nitrates are maximum in summer and minimum in winter. Alkalinity is more in monsoon and found less in winter. Comparatively higher values of conductivity, total alkalinity, chlorides, phosphates and nitrates in Malgujari pond of Ghugus is an indication of its contaminated status.